High-thermal-conductivity heat dissipation film and preparation method and application thereof
By using the calendering composite technology of the heat-diffusing layer of graphene and carbon nanotubes and the rod-shaped structure heat-diffusing layer in electronic equipment, a heat-diffusing film with high thermal conductivity and excellent spectral performance was prepared, which solved the problem of insufficient thermal conductivity in traditional cooling methods. , realizes effective heat dissipation of high-power electronic equipment.
Patent Information
- Application Number
- CN202410922356.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-07-10
- Publication Date
- 2024-12-17
AI Technical Summary
Traditional cooling methods have problems in electronic equipment, such as large volume, high noise, high cost and low reliability. Especially high-power electronic equipment is difficult to achieve effective heat dissipation, and the traditional thermal control film lacks thermal conductivity, resulting in heat accumulation and local hot spots. .
Using the calendering composite technology based on graphene and carbon nanotubes and the rod-shaped structure heat dissipation layer, high-refractive index rod-shaped micro-nano structural particles are prepared through high-temperature template assisted sintering, and conductive particles or thermally conductive particles are added to the heat dissipation layer. Combined with organic or inorganic binders, a high-thermal conductivity and heat dissipation film is formed.
It achieves high thermal conductivity (≧1300W/(m·K) and excellent spectral performance (solar spectral reflectivity ≧0.96, infrared wide band emissivity ≧0.93), and can effectively conduct and dissipate heat, suitable for high-power electronic equipment and The cooling requirements of spacecraft.
Smart Images

Figure CN119155953A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of electronic equipment thermal control, and in particular relates to a high thermal conductivity heat dissipation film and a preparation method and application thereof. Background Art
[0002] At present, the high integration of electronic components has led to an increase in power density, which will generate more heat inside the equipment. In addition, the external solar radiation will cause the operating temperature of electronic equipment to rise significantly, and excessively high operating temperature will have an adverse effect on the operating efficiency and service life of electronic equipment. In order to achieve operation within the normal temperature range, most electronic equipment uses air cooling systems or liquid cooling systems, but traditional cooling methods have some shortcomings in practical applications, such as large size, high noise, and limited cooling effect of air cooling systems; high cost, low reliability, and complex system structure of water cooling systems. Therefore, finding a new, efficient, and environmentally friendly heat dissipation method is the key to ensuring the normal operation of electronic equipment.
[0003] Unlike traditional active cooling methods, passive radiation cooling technology is an effective way to achieve heat dissipation of electronic equipment due to its characteristics of no energy input, no greenhouse gas emissions, and passive cooling. This cooling method mainly uses the unique spectral characteristics of materials. On the one hand, it reflects or scatters as much energy from the solar spectrum band as possible to suppress the heating effect of the sun on electronic equipment; on the other hand, it emits a large amount of infrared radiation energy through the atmospheric window to the space with a temperature close to absolute zero to release the heat generated by itself, thereby reducing the operating temperature of electronic equipment.
[0004] Although sub-ambient cooling can be achieved by radiation cooling, the cooling effect is limited. Especially for high-power electronic devices, it is difficult to achieve heat dissipation greater than the heat generated by themselves. This is mainly affected by two factors: 1) The reflectivity of the particles filled with existing films in the solar spectrum band and the emissivity in the infrared wide band are not ideal; 2) High-power electronic devices generate a lot of heat themselves, and local hot spots are prone to appear in the heat dissipation module. Due to the poor thermal conductivity of traditional thermal control films (thermal conductivity <1W / (m·K)), heat gradually accumulates locally on the surface of the device and cannot be diffused and discharged in time. Based on the above problems, inventing a micro-nano particle with high reflection in the ultraviolet-visible-near infrared band and high emission in the infrared wide band, and improving the thermal conductivity of the thermal control film are the key to meeting the heat dissipation needs of high-power electronic devices and even high-power spacecraft. Summary of the invention
[0005] The purpose of this section is to summarize some aspects of embodiments of the present invention and briefly introduce some preferred embodiments. Some simplifications or omissions may be made in this section and the specification abstract and the invention title of this application to avoid blurring the purpose of this section, the specification abstract and the invention title, and such simplifications or omissions cannot be used to limit the scope of the present invention.
[0006] In view of the above problems and / or the problems existing in the prior art, the present invention is proposed.
[0007] Therefore, the purpose of the present invention is to overcome the deficiencies in the prior art and provide a high thermal conductivity heat dissipation film.
[0008] In order to solve the above technical problems, the present invention provides the following technical solutions: comprising:
[0009] (i) A heat expansion layer based on graphene and carbon nanotubes and a heat dissipation layer based on a rod-like structure are obtained by calendering;
[0010] (ii) The rod-shaped structure-based heat dissipation layer is obtained by mixing and casting a dispersion and a continuum, wherein the dispersion is rod-shaped micro-nano structure particles, and the continuum includes an organic binder or an inorganic binder;
[0011] (iii) rod-shaped micro-nanostructured particles are prepared by combining two or more metal oxides with high refractive index and trace metal element oxides and then sintering them through high-temperature template assistance;
[0012] (iv) Metal oxides with a high refractive index include oxides of Si, Y, Zn, Zr, Ti, and Al, and trace metal element oxides include oxides of Hf, Ce, and Gd.
[0013] Furthermore, the electrical conductivity or thermal conductivity of the film can be improved by adding conductive particles or thermal conductive particles to the heat dissipation layer based on the rod-like structure, but the spectral performance of the film will be reduced accordingly.
[0014] As a preferred embodiment of the high thermal conductivity heat dissipation film described in the present invention, the side of the heat dissipation layer not compounded with the heat expansion layer is coated with a silicone protective layer, the side of the heat expansion layer not compounded with the heat dissipation layer is coated with a silicone backing adhesive, and a PET release film is also attached to the surface of the silicone backing adhesive.
[0015] As a preferred solution of the high thermal conductivity and heat dissipation film of the present invention, the thickness of the heat expansion layer is 20-50 μm, and the thickness of the heat dissipation layer is 100-500 μm.
[0016] As a preferred embodiment of the high thermal conductivity and heat dissipation film of the present invention, the organic binder includes one or more of silicone resin, polyurethane, fluorine-containing resin, and acrylic resin, and the inorganic binder includes one or more of potassium silicate, lithium silicate, sodium silicate, and aluminum dihydrogen phosphate.
[0017] As a preferred embodiment of the high thermal conductivity and heat dissipation film of the present invention, the thermal conductivity of the high thermal conductivity and heat dissipation film is ≧1300W / (m·K), the reflectivity of the entire solar spectrum is ≧0.96, the reflectivity of the ultraviolet band is ≧0.97, and the emissivity of the infrared wide band is ≧0.93.
[0018] Another object of the present invention is to provide a method for preparing a high thermal conductivity heat dissipation film.
[0019] In order to solve the above technical problems, the present invention provides the following technical solutions: comprising:
[0020] The graphene solution and the carbon nanotube solution are mixed to obtain slurry I, and after centrifugal film formation, thermal reduction treatment and graphitization treatment are performed in sequence to obtain a heat expansion layer;
[0021] Wherein, the treatment temperature of the thermal reduction treatment is 500-800°C, the treatment time is 3-6h, and the treatment temperature of the graphitization treatment is 2200-2600°C, the treatment time is 6-10h;
[0022] Two or more metal oxides with high refractive index and trace metal element oxides are combined and sintered at high temperature in an air atmosphere to obtain dispersed rod-shaped micro-nano structure particles;
[0023] The rod-shaped micro-nano structure particles are fully mixed with the continuum and then kneaded at a high temperature of 200° C. to 300° C. to obtain the dispersion / continuum hybrid particles;
[0024] The hybrid particles are extruded into a film at a high temperature of 200°C to 300°C to obtain a heat dissipation layer. During the extrusion process, the heat expansion layer is used as the base film, and a high thermal conductivity heat dissipation film is obtained through calendering and compounding.
[0025] As a preferred solution of the method for preparing the high thermal conductivity and heat dissipation film of the present invention, wherein: a silicone backing adhesive is coated on the side of the heat expansion layer that is not compounded with the heat dissipation layer and cured, and then a PET release film is attached, wherein the curing temperature is 100°C to 150°C, and the time is 1 to 5 minutes.
[0026] As a preferred embodiment of the method for preparing the high thermal conductivity and heat dissipation film of the present invention, the mass ratio of the solute in the graphene solution in the slurry I to the solute in the carbon nanotube solution is 1:1 to 1:0.5.
[0027] As a preferred solution of the method for preparing the high thermal conductivity and heat dissipation film of the present invention, the temperature of the high temperature sintering is 500-1700° C., and the sintering time is 0.5-5 hours.
[0028] Another object of the present invention is to provide an application of a high thermal conductivity and heat dissipation film in the preparation of high power electronic devices.
[0029] Beneficial effects of the present invention:
[0030] (1) The heat dissipation layer of the present invention can achieve synergistic coupling of the spectral performance of the solar band and the infrared wide band by introducing rod-shaped micro-nanostructure particles with high reflection in the solar band and high emission in the wide infrared band.
[0031] (2) The high thermal conductivity and heat dissipation film described in the present invention has the characteristics of good thermal conductivity and strong heat dissipation ability, which can conduct the heat on the surface of the device and dissipate it to the external environment in a timely manner.
[0032] (3) The high thermal conductivity and heat dissipation film described in the present invention has the characteristics of short assembly cycle, simple construction, and large-area preparation, and can meet the heat expansion / heat dissipation requirements of high-power electronic equipment and satellite-borne electronic devices. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the following briefly introduces the drawings required for describing the embodiments. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative labor. Among them:
[0034] Figure 1 It is a schematic structural diagram of the high thermal conductivity heat dissipation film of the present invention.
[0035] Figure 2 The figure is a flow chart of the preparation of the high thermal conductivity and heat dissipation film of the present invention.
[0036] Figure 3 This is a reflectivity spectrum of the high thermal conductivity and heat dissipation film prepared in Example 1 of the present invention in the solar band.
[0037] Figure 4 This is a spectrum diagram of the infrared wide-band emissivity of the high thermal conductivity and heat dissipation film prepared in Example 1 of the present invention. DETAILED DESCRIPTION
[0038] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the specific implementation methods of the present invention are described in detail below in conjunction with the embodiments of the specification.
[0039] In the following description, many specific details are set forth to facilitate a full understanding of the present invention, but the present invention may also be implemented in other ways different from those described herein, and those skilled in the art may make similar generalizations without violating the connotation of the present invention. Therefore, the present invention is not limited to the specific embodiments disclosed below.
[0040] Secondly, the term "one embodiment" or "embodiment" as used herein refers to a specific feature, structure, or characteristic that may be included in at least one implementation of the present invention. The term "in one embodiment" that appears in different places in this specification does not necessarily refer to the same embodiment, nor does it refer to a separate or selective embodiment that is mutually exclusive with other embodiments.
[0041] Unless otherwise specified, the raw materials used in the present invention are all commercially available in the art.
[0042] The film performance test in the present invention refers to:
[0043] Film solar band reflectivity: The equipment used is the American Agilent Cary5000 UV-visible-near infrared spectrophotometer, which can measure wavelengths from 190 to 3300 nm, with a wavelength resolution of 1 nm. The surface of the film sample measured is diffuse reflection, and the surface reflectivity measurement needs to be completed with the help of an integrating sphere accessory. Test conditions: atmospheric environment, room temperature (~25°C), relative humidity of 30% to 40%.
[0044] Film infrared wide-band emissivity: The equipment used is the V80v Fourier infrared spectrometer from Bruker, Germany, with a test wavelength range of 4000-400 (2.5-25 μm) and a resolution of 64 cm -1 The surface of the film sample to be measured is diffuse reflection, and the surface emissivity measurement needs to be completed with the help of an integrating sphere accessory. Test conditions: atmospheric environment, room temperature (~25°C), relative humidity of 30%~40%.
[0045] Film thermal conductivity: refer to GB / T 22588-2008 test standard.
[0046] Film resistivity: Refer to GB / T 1410-2006 test standard.
[0047] Example 1
[0048] Reference Figures 1-2 This embodiment provides a method for preparing a high thermal conductivity heat dissipation film, specifically:
[0049] 1) mixing a graphene solution and a carbon nanotube solution in a mass ratio of 1:0.6 to obtain a slurry I, and centrifugally forming a film at a speed of 1300 r / min using a centrifugal film-forming device;
[0050] The film was subjected to low-temperature thermal reduction treatment in a reducing atmosphere at a temperature of 500°C for 4 hours.
[0051] After reduction, the film was graphitized at high temperature by Joule heating at a temperature of 2400°C for 6 hours to obtain a heat expansion layer with a thickness of 30 μm.
[0052] 2) SiO2, Al2O3, and Gd2O3 powders are fully mixed to obtain a mixed powder, wherein the contents of SiO2, Al2O3, and Gd2O3 in the mixed powder are 49%, 49%, and 2%, respectively. The mixed powder is sintered at a high temperature in an air atmosphere at a reaction temperature of 1300° C. for a reaction time of 3 h to obtain dispersed rod-shaped micro-nanostructured particles;
[0053] The rod-like micro-nanostructured particles and the continuous silicone resin particles were fully mixed at a mass ratio of 1:5, and kneaded at 250° C. to obtain the dispersion / continuum hybrid particles;
[0054] The hybrid particles are extruded into a film at a high temperature of 250°C to obtain a heat dissipation layer with a thickness of 200 μm. During the extrusion process, the heat expansion layer obtained in step 1) is used as the base film, and a high thermal conductivity heat dissipation film is obtained through calendering and compounding.
[0055] 3) Using a coating machine, a silicone adhesive is coated on the side of the heat expansion layer of the high thermal conductivity heat dissipation film prepared in step 2) that is not composited with the heat dissipation layer, and the film is cured at 130° C. for 2 minutes. After curing, a layer of PET release film with a thickness of 30 μm is attached to the surface.
[0056] Example 2
[0057] 1) mixing a graphene solution and a carbon nanotube solution in a mass ratio of 1:0.8 between graphene and carbon nanotubes to obtain a slurry I, and centrifugally forming a film at a speed of 1400 r / min using a centrifugal film-forming device;
[0058] The film was subjected to low-temperature thermal reduction treatment in a reducing atmosphere at a temperature of 600°C for 4 hours.
[0059] After reduction, the film was graphitized at high temperature by Joule heating at a temperature of 2300°C for 6 hours to obtain a heat expansion layer with a thickness of 30 μm.
[0060] 2) SiO2, ZnO and CeO2 powders are fully mixed to obtain a mixed powder, wherein the contents of SiO2, ZnO and CeO2 in the mixed powder are 49%, 49% and 2% respectively, and the mixed powder is sintered at a high temperature in an air atmosphere at a reaction temperature of 1100° C. for a reaction time of 3 h to obtain dispersed rod-shaped micro-nanostructured particles;
[0061] The rod-like micro-nanostructured particles and the continuous acrylic resin particles were fully mixed at a mass ratio of 1:5, and kneaded at 200°C to obtain the dispersion / continuum hybrid particles;
[0062] The hybrid particles are extruded at 200°C to form a film to obtain a heat dissipation layer with a thickness of 200 μm. During the extrusion process, the heat expansion layer obtained in step 1) is used as the base film, and a high thermal conductivity heat dissipation film is obtained by calendering and compounding.
[0063] 3) Using a coating machine, a silicone adhesive is coated on the side of the heat expansion layer of the high thermal conductivity heat dissipation film prepared in step 2) that is not composited with the heat dissipation layer, and the film is cured at 120° C. for 2 minutes. After curing, a layer of PET release film with a thickness of 30 μm is attached to the surface.
[0064] Example 3
[0065] 1) mixing a graphene solution and a carbon nanotube solution in a mass ratio of 1:1 between graphene and carbon nanotubes to obtain a slurry I, and centrifugally forming a film at a speed of 1500 r / min using a centrifugal film-forming device;
[0066] The film was subjected to low-temperature thermal reduction treatment in a reducing atmosphere, with a reduction temperature of 700°C and a reduction time of 4 hours.
[0067] After reduction, the film was subjected to high-temperature graphitization treatment by Joule heating at a temperature of 2200°C for 6 hours to obtain a heat expansion layer with a thickness of 30 μm.
[0068] 2) SiO2, Y2O3, and HfO2 powders are fully mixed to obtain a mixed powder, wherein the contents of SiO2, Y2O3, and HfO2 in the mixed powder are 49%, 49%, and 2%, respectively. The mixed powder is sintered at a high temperature in an air atmosphere at a reaction temperature of 1200° C. for a reaction time of 2 h to obtain dispersed rod-shaped micro-nanostructured particles;
[0069] The rod-like micro-nanostructured particles and the continuum polyurethane particles were fully mixed at a mass ratio of 1:5, and kneaded at 220°C to obtain the dispersion / continuum hybrid particles;
[0070] The hybrid particles are extruded into a film at a high temperature of 220° C. to obtain a heat dissipation layer with a thickness of 200 μm. During the extrusion process, the heat expansion layer obtained in step 1) is used as the base film, and a high thermal conductivity heat dissipation film is obtained by calendering and compounding.
[0071] 3) Using a coating machine, a silicone adhesive is coated on the side of the heat expansion layer of the high thermal conductivity heat dissipation film prepared in step 2) that is not composited with the heat dissipation layer, and the film is cured at 150° C. for 1 min. After curing, a layer of PET release film with a thickness of 30 μm is attached to the surface.
[0072] Example 4
[0073] In this embodiment, an antistatic and high thermal conductivity heat dissipation film for high-power electronic equipment is prepared by doping AZO conductive particles into the heat dissipation layer. Specifically:
[0074] 1) mixing a graphene solution and a carbon nanotube solution in a solute mass ratio of 1:0.8 to obtain a slurry I, and centrifugally forming a film at a speed of 1300 r / min using a centrifugal film-forming device;
[0075] The film was subjected to low-temperature thermal reduction treatment in a reducing atmosphere, with a reduction temperature of 600°C and a treatment time of 4 hours.
[0076] After reduction, the film was graphitized at high temperature by Joule heating at a temperature of 2300°C for 6 hours to obtain a heat expansion layer with a thickness of 30 μm.
[0077] 2) SiO2, ZnO and Gd2O3 powders are fully mixed to obtain a mixed powder, wherein the contents of SiO2, ZnO and Gd2O3 in the mixed powder are 49%, 49% and 2% respectively, and the mixed powder is sintered at a high temperature in an air atmosphere at a reaction temperature of 1200°C for a reaction time of 2 hours to obtain dispersed rod-shaped micro-nanostructured particles;
[0078] The rod-like micro-nanostructure particles and the continuous acrylic resin particles are fully mixed at a mass ratio of 1:5, 20 wt % of AZO conductive particles are added, and the mixture is kneaded at 260° C. to obtain the dispersion / continuum hybrid particles;
[0079] The hybrid particles are extruded at 260°C to form a film to obtain a heat dissipation layer with a thickness of 200 μm. During the extrusion process, the heat expansion layer obtained in step 1) is used as the base film, and a high thermal conductivity heat dissipation film is obtained by calendering and compounding.
[0080] 3) Using a coating machine, a silicone adhesive is coated on the side of the heat expansion layer of the high thermal conductivity heat dissipation film prepared in step 2) that is not composited with the heat dissipation layer, and the film is cured at 140° C. for 1 min. After curing, a layer of PET release film with a thickness of 30 μm is attached to the surface.
[0081] Example 5
[0082] In this embodiment, a high thermal conductivity heat dissipation film for satellite-borne high-power electronic equipment is prepared by coating an organic silicon protective layer on the side of the film where the heat dissipation layer is not compounded with the heat expansion layer. Specifically:
[0083] 1) mixing a graphene solution and a carbon nanotube solution in a solute mass ratio of 1:1 to obtain a slurry I, and centrifugally forming a film at a speed of 1500 r / min using a centrifugal film-forming device;
[0084] The film was subjected to low-temperature thermal reduction treatment in a reducing atmosphere, with a reduction temperature of 700°C and a treatment time of 4 hours.
[0085] After reduction, the film was graphitized at high temperature by Joule heating at a temperature of 2200°C for 6 hours to obtain a heat expansion layer with a thickness of 30 μm.
[0086] 2) SiO2, Y2O3, and HfO2 powders are fully mixed to obtain a mixed powder, wherein the contents of SiO2, Y2O3, and HfO2 in the mixed powder are 49%, 49%, and 2%, respectively. The mixed powder is sintered at a high temperature in an air atmosphere at a reaction temperature of 1200° C. for a reaction time of 2 h to obtain dispersed rod-shaped micro-nanostructured particles;
[0087] The rod-like micro-nanostructured particles and the continuous fluorine-containing resin particles are fully mixed at a mass ratio of 1:5, and kneaded at 250° C. to obtain the dispersion / continuum hybrid particles;
[0088] The hybrid particles are extruded into a film at a high temperature of 250°C to obtain a heat dissipation layer with a thickness of 200 μm. During the extrusion process, the heat expansion layer obtained in step 1) is used as the base film, and a high thermal conductivity heat dissipation film is obtained through calendering and compounding.
[0089] 3) The side of the heat dissipation layer of the high thermal conductivity heat dissipation film prepared in step 2) that is not composited with the heat expansion layer is coated with an organic silicon protective layer, which is cured at 80° C. and has a layer thickness of 0.4 μm.
[0090] The side of the heat expansion layer of the high thermal conductivity heat dissipation film prepared in step 2) that is not composited with the heat dissipation layer is coated with silicone adhesive by a coating machine, and cured at 150° C. for 1 min. After curing, a layer of PET release film with a thickness of 30 μm is attached to its surface.
[0091] Example 6
[0092] In this embodiment, a high thermal conductivity heat dissipation film for high-power electronic equipment is prepared by doping high thermal conductivity boron nitride particles into the heat dissipation layer. Specifically:
[0093] 1) mixing a graphene solution and a carbon nanotube solution in a solute mass ratio of 1:1 to obtain a slurry I, and centrifugally forming a film at a speed of 1300 r / min using a centrifugal film-forming device;
[0094] The film was subjected to low-temperature thermal reduction treatment in a reducing atmosphere, with a reduction temperature of 600°C and a treatment time of 4 hours.
[0095] After reduction, the film was graphitized at high temperature by Joule heating at a temperature of 2300°C for 6 hours to obtain a heat expansion layer with a thickness of 30 μm.
[0096] 2) SiO2, ZrO2, and CeO2 powders are fully mixed to obtain a mixed powder, wherein the contents of SiO2, ZrO2, and CeO2 in the mixed powder are 49%, 49%, and 2%, respectively. The mixed powder is sintered at a high temperature in an air atmosphere at a reaction temperature of 1400° C. for a reaction time of 3 h to obtain dispersed rod-shaped micro-nanostructured particles;
[0097] The rod-shaped micro-nanostructured particles and the continuous fluorine-containing resin particles are fully mixed at a mass ratio of 1:5, 20 wt % of high thermal conductivity boron nitride particles are added, and the mixture is kneaded at 260° C. to obtain the dispersion / continuum hybrid particles;
[0098] The hybrid particles are extruded at 260°C to form a film to obtain a heat dissipation layer with a thickness of 200 μm. During the extrusion process, the heat expansion layer obtained in step 1) is used as the base film, and a high thermal conductivity heat dissipation film is obtained by calendering and compounding.
[0099] 3) Using a coating machine, a silicone adhesive is coated on the side of the heat expansion layer of the high thermal conductivity heat dissipation film obtained in step 2) that is not composited with the heat dissipation layer, and the film is cured at 140° C. for 2 minutes. After curing, a layer of PET release film with a thickness of 30 μm is attached to the surface.
[0100] The relevant properties of the finished films obtained in Examples 1 to 6 were tested, and the results are shown in Table 1.
[0101] Table 1
[0102]
[0103]
[0104] (Note: “-” indicates that the resistivity is too high and cannot achieve the “antistatic” effect. The antistatic requirement is that the resistivity is no higher than 1×10 7 )
[0105] It can be seen from Table 1 that the high thermal conductivity and heat dissipation film prepared by the present invention has the characteristics of good thermal conductivity and strong heat dissipation ability, which is achieved by introducing high-reflection and high-emission rod-shaped micro-nano structure particles prepared by template-assisted sintering process into the heat dissipation layer, and compounding a heat expansion layer under the heat dissipation layer; it can be seen from Examples 1 to 3 that the rod-shaped particles sintered from different material systems have a certain influence on the spectral properties after film formation; it can be seen from Examples 4 to 6 that by adding conductive particles / high thermal conductivity particles to the heat dissipation layer and compounding an organic silicon protective layer on the surface of the heat dissipation layer, the functions of the thermal control film in anti-static, dimensional stability, and high thermal conductivity can be extended, thereby broadening its application range.
[0106] Example 7
[0107] This example is used to explore the influence of the sintering temperature of the rod-shaped micro-nano structure particles on the technical effect during the preparation of the high thermal conductivity and heat dissipation film. Specifically, the high temperature sintering temperature of the rod-shaped micro-nano structure particles in step 2) of Example 1 is adjusted to 500, 700, 900, 1100, 1500, and 1700°C, respectively. The remaining steps and processes are all referred to Example 1, and the films under different sintering temperature conditions of this example are obtained. The relevant performance tests are performed on them and compared with 1300°C in Example 1. The results are shown in Table 2.
[0108] Table 2
[0109] Sintering temperature UV reflectivity Solar band reflectivity Infrared broadband emissivity 500℃ 0.81 0.80 0.88 700℃ 0.89 0.88 0.89 900℃ 0.94 0.92 0.93 1100℃ 0.95 0.95 0.93 1300℃ 0.98 0.98 0.93 1500℃ 0.96 0.96 0.93 1700℃ 0.89 0.89 0.90
[0110] It can be seen from Table 2 that the sintering temperature of the rod-shaped micro-nanostructure particles has a significant effect on the spectral performance of the high thermal conductivity and heat dissipation film. When the sintering temperature is too low or too high, it will have a negative impact on the spectral performance of the film. Only at the appropriate reaction temperature can the spectral performance of the film reach the best.
[0111] Example 8
[0112] This example is used to explore the influence of the sintering time of rod-shaped micro-nanostructure particles on the technical effect during the preparation of high thermal conductivity and heat dissipation film. Specifically, the high temperature sintering time of the rod-shaped micro-nanostructure particles in step 2) of Example 1 is adjusted to 0.5, 1, 2, 4, and 5 h, respectively. The remaining steps and processes are all referred to Example 1, and the films under different sintering time conditions of this example are obtained. The relevant performance tests are carried out and compared with 3 h in Example 1. The results are shown in Table 3.
[0113] Table 3
[0114] Sintering time UV reflectivity Solar band reflectivity Infrared broadband emissivity 0.5h 0.86 0.86 0.89 1h 0.95 0.93 0.93 2h 0.96 0.95 0.93 3h 0.98 0.98 0.93 4h 0.96 0.96 0.93 5h 0.89 0.88 0.89
[0115] It can be seen from Table 3 that the sintering time of rod-shaped micro-nanostructure particles has a significant effect on the spectral properties of the high thermal conductivity and heat dissipation film. When the sintering time is too long or too short, it will have a negative impact on the spectral properties of the film. Only when the sintering time is appropriate, the spectral properties of the film can reach the best.
[0116] It should be noted that the solar band reflectivity and infrared band emissivity are indirect manifestations of the film's "heat dissipation function". The higher the reflectivity, the less solar energy is absorbed, and the higher the emissivity, the more heat is emitted. The value can reflect the film's heat dissipation ability. In the field of radiation cooling, it is generally believed that the reflectivity must be above 0.9 to achieve a real cooling effect, so even a 2% increase will have a significant effect.
[0117] Comparative Example 1
[0118] The difference between this comparative example and Example 1 is that no heat expansion layer is prepared, and only a single heat dissipation layer is prepared. Specifically:
[0119] 1) SiO2, Al2O3, and Gd2O3 powders are fully mixed to obtain a mixed powder, wherein the contents of SiO2, Al2O3, and Gd2O3 in the mixed powder are 49%, 49%, and 2%, respectively. The mixed powder is sintered at a high temperature in an air atmosphere at a reaction temperature of 1300° C. for a reaction time of 3 h to obtain dispersed rod-shaped micro-nanostructured particles;
[0120] The rod-like micro-nanostructured particles and the continuous fluorine-containing resin particles are fully mixed at a mass ratio of 1:5, and kneaded at 250° C. to obtain the dispersion / continuum hybrid particles;
[0121] The hybrid particles were extruded at 250°C to form a film, thereby obtaining a heat dissipation layer film with a thickness of 200 μm.
[0122] Comparative Example 2
[0123] The difference between this comparative example and Example 1 is that the metal oxide is not sintered but directly doped. Specifically, step 2) of Example 1 is adjusted as follows:
[0124] SiO2, Al2O3, and Gd2O3 powders are fully mixed to obtain a mixed powder, wherein the contents of SiO2, Al2O3, and Gd2O3 in the mixed powder are 49%, 49%, and 2%, respectively; the mixed powder is fully mixed with continuous fluorine-containing resin particles at a mass ratio of 1:5, and kneaded at 250° C. to obtain dispersion / continuum hybrid particles;
[0125] The hybrid particles were extruded at 250°C to form a film to obtain a heat dissipation layer with a thickness of 200 μm. During the extrusion process, the heat expansion layer was used as the base film and calendered to obtain the thermal control film of this comparative example.
[0126] The properties of the films obtained in Comparative Examples 1 and 2 were tested and compared with those in Example 1. The results are shown in Table 4.
[0127] Table 4
[0128] UV reflectivity Solar band reflectivity Infrared broadband emissivity Thermal conductivity (W / (m·K)) Example 1 0.98 0.98 0.93 1350 Comparative Example 1 0.98 0.98 0.93 0.5 Comparative Example 2 0.91 0.90 0.91 1350
[0129] It can be seen from Table 4 that the thermal control film in Comparative Example 1 in which the heat expansion layer is not introduced has a lower thermal conductivity, and cannot have the characteristics of good thermal conductivity and strong heat dissipation capacity; in Comparative Example 2, the raw materials are not subjected to high-temperature template-assisted sintering, and the spectral performance of the thermal control film is poor, and it also cannot have the characteristics of good thermal conductivity and strong heat dissipation capacity. It can be seen that the present application improves the spectral performance of particles / films by sintering, and composites the graphene heat expansion layer and the heat dissipation layer to synergistically improve the performance of the thermal control film.
[0130] In summary, the high thermal conductivity and heat dissipation film prepared by the present invention has the characteristics of good thermal conductivity and strong heat dissipation capacity, can realize the synergistic coupling of the solar light band and the infrared wide-band spectral performance, has the characteristics of short assembly cycle, simple construction, and large-area preparation, and can meet the heat expansion / heat dissipation needs of high-power electronic equipment and satellite / aircraft / shipborne heat dissipation group components.
[0131] It should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solutions of the present invention may be modified or replaced by equivalents without departing from the spirit and scope of the technical solutions of the present invention, which should all be included in the scope of the claims of the present invention.
Claims
1. A high thermal conductivity heat dissipation film, characterized in that: include, (i) A heat expansion layer based on graphene and carbon nanotubes and a heat dissipation layer based on a rod-like structure are obtained by calendering. (ii) The rod-shaped structure-based heat dissipation layer is obtained by mixing and casting a dispersion and a continuum, wherein the dispersion is rod-shaped micro-nano structure particles, and the continuum includes an organic binder or an inorganic binder; (iii) rod-shaped micro-nanostructured particles are prepared by combining two or more metal oxides with high refractive index and trace metal element oxides and then sintering them through high-temperature template assistance; (iv) Metal oxides with a high refractive index include oxides of Si, Y, Zn, Zr, Ti, and Al, and trace metal element oxides include oxides of Hf, Ce, and Gd.
2. The high thermal conductivity heat dissipation film according to claim 1, characterized in that: The side of the heat dissipation layer not compounded with the heat expansion layer is coated with an organic silicon protective layer, and the side of the heat expansion layer not compounded with the heat dissipation layer is coated with an organic silicon backing glue, and a PET release film is also attached to the surface of the organic silicon backing glue.
3. The high thermal conductivity heat dissipation film according to claim 2, characterized in that: The thickness of the heat expansion layer is 20-50 μm, and the thickness of the heat dissipation layer is 100-500 μm.
4. The high thermal conductivity heat dissipation film according to claim 1, characterized in that: The organic binder includes one or more of silicone resin, polyurethane, fluorine-containing resin, and acrylic resin, and the inorganic binder includes one or more of potassium silicate, lithium silicate, sodium silicate, and aluminum dihydrogen phosphate.
5. The high thermal conductivity heat dissipation film according to any one of claims 1 to 4, characterized in that: The high thermal conductivity heat dissipation film has a thermal conductivity of ≧1300 W / (m·K), a reflectivity of the entire solar spectrum of ≧0.96, a reflectivity of the ultraviolet band of ≧0.97, and an infrared broadband emissivity of ≧0.
93.
6. The method for preparing a high thermal conductivity heat dissipation film according to claim 5, characterized in that: include, The graphene solution and the carbon nanotube solution are mixed to obtain slurry I, and after centrifugal film formation, thermal reduction treatment and graphitization treatment are performed in sequence to obtain a heat expansion layer; Wherein, the treatment temperature of the thermal reduction treatment is 500-800°C, the treatment time is 3-6h, and the treatment temperature of the graphitization treatment is 2200-2600°C, the treatment time is 6-10h; Two or more metal oxides with high refractive index and trace metal element oxides are combined and sintered at high temperature in an air atmosphere to obtain dispersed rod-shaped micro-nano structure particles; The rod-shaped micro-nano structure particles are fully mixed with the continuum and then kneaded at a high temperature of 200° C. to 300° C. to obtain the dispersion / continuum hybrid particles; The hybrid particles are extruded into a film at a high temperature of 200°C to 300°C to obtain a heat dissipation layer. During the extrusion process, the heat expansion layer is used as the base film, and a high thermal conductivity heat dissipation film is obtained through calendering and compounding.
7. The method for preparing a high thermal conductivity heat dissipation film according to claim 6, characterized in that: The side of the heat expansion layer that is not compounded with the heat dissipation layer is coated with an organic silicon adhesive and cured, and then a PET release film is attached, wherein the curing temperature is 100° C. to 150° C. and the curing time is 1 to 5 minutes.
8. The method for preparing a high thermal conductivity heat dissipation film according to claim 6, characterized in that: The mass ratio of the solute in the graphene solution and the carbon nanotube solution in the slurry I is 1:1 to 1:0.
5.
9. The method for preparing a high thermal conductivity heat dissipation film according to claim 6, characterized in that: The high temperature sintering temperature is 500-1700° C., and the sintering time is 0.5-5 hours.
10. Use of the high thermal conductivity and heat dissipation film according to claim 5 in the preparation of high-power electronic devices.
